(untitled) (Revista Contexto & Saúde, 2026)
Objective: To analyze the quality of life of older adults with self-reported hypertension. correlating it with sociodemographic and clinical aspects. Method: Cross-sectional and analytical study. Data were collected between June and November 2021 through interviews using instruments containing sociodemographic and clinical profile data, the World Health Organization Quality of Life Brief (WHOQOL-BREF) and Whoqol-old. The Mann-Whitney test was used to compare the domains of the Whoqol-Bref and Whoqol-old between sexes. The chi-square and Fisher’s exact tests were applied to verify equality in the sociodemographic and clinical characteristics of the sexes. The relationship between the QoL scores of the Whoqol-Bref and Whoqol-old was verified by Spearman’s correlation. A significance level of 5% was considered for all statistical tests. Results: The Whoqol-Bref showed that female participants had lower quality of life scores, ranging from 3.3 to 3.7, compared to males (3.7 to 4.0). In the physical aspect, a lower score was observed in females (median=3.3), with a statistically significant difference compared to males (median=3.7; p<0.001). In the overall quality of life score, men obtained a higher score (median=3.8) compared to women (median=3.5), a statistically significant difference between the sexes (p=0.003). Conclusion: The quality of life of older women is significantly worse compared to that of older men, and this constitutes an important element for planning interventions in the field of health.